NMR structures and molecular dynamics simulation of hylin-a1 peptide analogs interacting with micelles - Crusca, Edson [UNESP]; Câmara, Amanda Souza; Matos, Carolina Oliveira; Marchetto, Reinaldo [UNESP]; Cilli, Eduardo Maffud [UNESP]; Lião, Luciano Morais; Lima de Oliveira, Aline (Wiley, 2017)
Antimicrobial peptides are recognized candidates with pharmaceutical potential against epidemic emerging multi-drug resistant bacteria. In this study, we use nuclear magnetic resonance spectroscopy and molecular dynamics simulations to determine the unknown structure and evaluate the interaction with dodecylphosphatidylcholine (DPC) and sodium dodecylsulphate (SDS) micelles with three W6-Hylin-a1 analogs antimicrobial peptides (HyAc, HyK, and HyD). The HyAc, HyK, and HyD bound to DPC micelles are all formed by a unique α-helix structure. Moreover, all peptides reach the DPC micelles' core, which thus suggests that the N-terminal modifications do not influence the interaction with zwiterionic surfaces. On the other hand, only HyAc and HyK peptides are able to penetrate the SDS micelle core while HyD remains always at its surface. The stability of the α-helical structure, after peptide-membrane interaction, can also be important to the second step of peptide insertion into the membrane hydrophobic core during permeabilization. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: antimicrobial peptides; DPC; molecular dynamics simulations; NMR; SDS; W6-Hylin-a1 analogs